Using Ground Penetrating Radar to Monitor Seasonal Moisture Fluctuations in Base Layers of Existing Roads. Issue 6 (June 2022) - Zegeye-Teshale, Eyoab; Holzbauer, Micah; Dai, Shongtao
A high moisture content in the unbound aggregate layers of pavements can lead to severe functional and structural damage, especially in pavement constructed in freeze-thaw environments, such as Minnesota. In these climates, the freezing temperatures can contribute to the formation of severe crack-heaving issues, and the early spring-thaw conditions can significantly reduce a pavement's bearing capacity. A good understanding of subsurface seasonal moisture fluctuation is, therefore, essential for implementing effective maintenance and road load management techniques. Unfortunately, traditional pavement moisture testing approaches are expensive, time-consuming, invasive, limited in spatial coverage, and negatively affect the traffic flow. The present study builds on previous efforts to characterize moisture and frost conditions in pavement base layers using ground penetrating radar (GPR) and moisture sensing instruments. The paper offers a simple methodology for monitoring moisture variations in the base layer and assessing the moisture susceptibility of aggregate base materials from single-offset GPR measurements. The methodology was validated by comparing the GPR data with moisture content readings collected from four different pavement test sections over a period of approximately two years. Overall, the moisture contents obtained from the GPR were comparable with those obtained from sensors installed in the pavement section. However, the GPR approach offered the added advantage of covering long stretches of pavement in short times and with minimal impact on the pavement and traffic.